A large deviation principle for a natural sequence of point processes on a Riemannian two-dimensional manifold - García Zelada, David (Pontificia Universidad Católica del Perú, 2018)
Siguiendo las tecnicas desarrolladas por Paul Dupuis, Vaios Laschos y Kavita Ramanan en [8], se establecera un principio de grandes desviaciones para una secuencia de procesos puntuales denidos por medidas de Gibbs en una variedad riemanniana bidimensional compacta y orientable. Veremos que la correspondiente secuencia de medidas empíricas converge a la solucion de una ecuacion diferencial parcial y, en ciertos casos, a la forma de volumen de una metrica de curvatura constante.

We follow the techniques of Paul Dupuis, Vaios Laschos, and Kavita Ramanan in [8] to prove a large deviation principle for a sequence of point processes dened by Gibbs measures on a compact orientable two- dimensional Riemannian manifold. We see that the corresponding sequence of empirical measures converges to the solution of a partial differential equation and, in some cases, to the volume form of a constant curvature metric.
Keywords: Desviación grande; https://purl.org/pe-repo/ocde/ford#1.01.00